Spontaneous Perforation of a Malignified Corrosive Stricture of the Esophagus and Subsequent Perforation of a Giant Duodenal Stress ULCUS - Yankov G. (Acta Medica Bulgarica, 2020)
Surgical interventions for corrosive stricture of the esophagus are extremely difficult and technically challenging. In this manuscript, we present a patient with esophagectomy due to perforation of a corrosive stricture of the esophagus that underwent malignant transformation and subsequent perforation of a giant duodenal stress ulcus, which occurred 12 days after the intervention. We performed a total esophagectomy, pharyngo- and gastrostomy, suture of the duodenal perforation but the postoperative period was challenging and despite our efforts, the patient died on the 50th postoperative day due to respiratory and renal failure.